Weather station analysis using microcontroller and internet of things (IOT) - Fook, Wei Jian (2017)
The monitoring of weather is really helpful in various applications like in critical scientific systems or for simulation purposes. Weather monitoring device is a small size, portable and stand-alone electronic device. Weather monitoring device consists of Arduino Mega, Wi-Fi shield and a temperature sensor. The parameters collected were room air temperature and relative humidity of a particular area. Data collected from sensor will be used to calculate dew point temperature which is important to determine the human perception on current weather. The collected data will be sent to Thingspeak, an Internet of Things (loT) website to display and monitor the data in the form of real-time graph. Collected data show accurate real-time values that represent the current weather condition of the area being measured. Besides, the relationship between room air temperature, relative humidity and dew point temperature can be determined. Lastly, the human perception among Malaysian on current weather condition can be determined through dew point temperature which is included in this project.